Psychometric performance of the WHOQOL-HIV BREF among people living with HIV on antiretroviral therapy in Bauchi State, Nigeria - Ekerette Emmanuel Udoh; Adesola Zaidat Musa; Tubosun Alex Olowolafe; Taiwao Mofadeke Jaiyeola (PLoS ONE, 2025)
Background The well-being of people living with HIV (PLHIV) remains a significant public health concern. Despite advancements in ART, PLHIV face various challenges impacting their quality of life (QOL). Measuring the QOL of PLHIV is essential for improving care, shaping policy, and evaluating intervention. However, the extent to which the measurement properties of the World Health Organization Quality of Life HIV BREF (WHOQOL-HIV BREF) tool, in the Nigeria context is limited. This study evaluated the psychometric performance of the WHOQOL-HIV BREF in a Nigerian population, with the aim of examining its construct validity, reliability, and sensitivity when used to assess the well-being of PLHIV. Methods This was a cross-sectional quantitative study involving of 790 PLHIV aged 18 years and older in Bauchi State, Nigeria. Data was collected between May and October 2023. Quality of life was assessed using the 31-item WHOQOL-HIV BREF which assesses QOL based on the 6 domains, including Physical, Psychological, Level of Independence, Social Relationships, Environmental, and Spirituality/Religion/Personal Beliefs. The general quality of life and general health perception was also assessed. The psychometric evaluation of the instrument in this population included analyses of internal consistency reliability, confirmatory factor analysis (CFA) to assess construct validity, and sensitivity analysis to examine measurement responsiveness. Results Confirmatory factor analysis of the WHOQOL-HIV BREF in the sample indicated poor model fit (CFI = 0.807, TLI = 0.767, RMSEA = 0.110, SRMR = 0.136), indicating that the original six-domain structure was not well supported in the study population and context. Internal consistency (Cronbach’s alpha) varied widely across domains, ranging from very low to acceptable: Physical Health (α = 0.386), Psychological Health (α = 0.722), Level of Independence (α = 0.531), Social Relationships (α = 0.693), Environment (α = 0.775), and Spirituality (α = 0.304). The Global Quality of Life score demonstrated high reliability (α = 0.884). Nonetheless, high scores were observed for general quality of life (Mean = 3.86) and health perception (Mean = 3.65), as well as for independence (Mean = 14.84) and social relationships (Mean = 14.93). Moderate scores were found in physical health (Mean = 13.99), psychological health (Mean = 13.95), environmental (Mean = 12.74), and spiritual well-being (Mean = 13.77). Conclusions This study revealed limited structural validity and varied internal consistency in this sample, with some domains of the WHOQOL-HIV BREF performing poorly. These findings reinforce concerns raised by researchers about the use of the tool without proper contextual adaptation. Further research is needed to better understand QOL in the Nigeria population, by refining and validating the QOL assessment tools for the country, to ensure adequate monitoring of the health of PLHIV.